CHARACTERISTICS OF SEED OIL EXTRACTED FROM SEVERAL KENAF (Hibiscus cannabinus L.) GENOTYPES FOR MEDICINE AND FOOD TRAITS - Salih , Rabar F. (Science Journal of University of Zakho, 2024)
Kenaf plant (Hibiscus cannabinus L.) was selected as plant material since it has great value for food and medicine purposes. This current study aims to evaluate the kenaf seed oils extracted (fatty acids) in six genotypes and then to indicate their benefits in cooking and medicinal uses. In the summer season of 2022, seeds of kenaf (FH952, HC95, HC2, 4383, 4202, and V36) were collected after harvesting. Results showed that FH952 is superior on others by having great values of oil, protein, and fatty acids (palmitic, stearic, oleic, linoleic, linolenic) by (29.0, 19.4, 8.8, 2.9, 21.9, 57.3, and 0.9 %), respectively, except of 4383 was recorded the same results in cases of palmitic and linolenic fatty acids. Despite that, the highest smoke point value found in HC95 by almost (400 °F). Inversely, V36 had the lowest position for all study characteristic with observed few similarities in some fatty acids. Generally, having these values of omega-3,6,9 fatty acids were extracted of all kenaf seed oils display the impact of this crop and could considered as a natural edible oil.
Keywords: Kenaf seeds; Fatty acids; Omega-3-6-9; Protein; Oil smoke point; Medicinal plants